The elements of style - Strunk, William 1869-1946.; White, E. B. (Elwyn Brooks) 1899-1985.; Kalman, Maira (New York Penguin Press, 2007)
An enhanced edition of the classic writing manual features humorous art by a popular children's book illustrator and New Yorker cover artist, in a volume that provides visual and whimsical embellishments to the original instructive text--Publisher.
Keywords: English language -- Rhetoric; English language -- Style; Report writing